À Saint-Tricat, l’église de Saint-Nicaise unique témoin d’un passé agité (La Voix du Nord, 2018)
Keywords: saint-tricat

L’Abbazia di S. Pietro di Licusati, antico cenobio basiliano - Attanasio, Francesco (Sapri roui nata, 2018)
Keywords: camerota

Äbte und Chorherren des Prämonstratenserstifts Steinfeld, Teil 1 - Joester, Ingrid (Germania Sacra, 2018)
Das Kloster Steinfeld in der Eifel im Erzbistum Köln wurde im 10. oder 11. Jahrhundert gegründet und schloss sich zwischen 1136 und 1142 dem Prämonstratenserorden an. Steinfeld galt als Tochterkloster von Prémontré und nahm schon bald eine führende Stellung in der Zirkarie Westfalen ein. Die Bedeutung Steinfelds kommt darin zum Ausdruck, dass die Äbte im 15. und 16. Jahrhundert vom Generalkapitel umfangreiche Aufträge zu Visitation und Reform anderer Ordensstifte erhielten und durchführten und dass sie vom 17. Jahrhundert bis zur Aufhebung im Jahr 1802 als Generalvikare des Abtes von Prémontré in den Zirkarien Westfalen, Ilfeld und Wadgassen mit weitreichenden Vollmachten fungierten. Der hier publizierte Personenkatalog liefert in zwei Teilbänden Informationen zum Personal des Konvents. Die Viten der Pröpste und Äbte sind im ersten Teil abgehandelt, der zweite Teil enthält die biographischen Informationen zu den Chorherren des Stifts. Die Besitzungen des Prämonstratenserstifts Steinfeld sind separat im dritten Supplementband der Germania Sacra aufgearbeitet.
Keywords: steinfeld

Äbte und Chorherren des Prämonstratenserstifts Steinfeld, Teil 2 - Joester, Ingrid (Germania Sacra, 2018)
Das Kloster Steinfeld in der Eifel im Erzbistum Köln wurde im 10. oder 11. Jahrhundert gegründet und schloss sich zwischen 1136 und 1142 dem Prämonstratenserorden an. Steinfeld galt als Tochterkloster von Prémontré und nahm schon bald eine führende Stellung in der Zirkarie Westfalen ein. Die Bedeutung Steinfelds kommt darin zum Ausdruck, dass die Äbte im 15. und 16. Jahrhundert vom Generalkapitel umfangreiche Aufträge zu Visitation und Reform anderer Ordensstifte erhielten und durchführten und dass sie vom 17. Jahrhundert bis zur Aufhebung im Jahr 1802 als Generalvikare des Abtes von Prémontré in den Zirkarien Westfalen, Ilfeld und Wadgassen mit weitreichenden Vollmachten fungierten. Der hier publizierte Personenkatalog liefert in zwei Teilbänden Informationen zum Personal des Konvents. Die Viten der Pröpste und Äbte sind im ersten Teil abgehandelt, der zweite Teil enthält die biographischen Informationen zu den Chorherren des Stifts. Die Besitzungen des Prämonstratenserstifts Steinfeld sind separat im dritten Supplementband der Germania Sacra aufgearbeitet.
Keywords: steinfeld

Der Besitz des Prämonstratenserstifts Steinfeld - Joester, Ingrid (Germania Sacra, 2018)
Das Kloster Steinfeld in der Eifel im Erzbistum Köln wurde im 10. oder 11. Jahrhundert gegründet und schloss sich zwischen 1136 und 1142 dem Prämonstratenserorden an. Steinfeld galt als Tochterkloster von Prémontré und nahm schon bald eine führende Stellung in der Zirkarie Westfalen ein. Die Bedeutung Steinfelds kommt darin zum Ausdruck, dass die Äbte im 15. und 16. Jahrhundert vom Generalkapitel umfangreiche Aufträge zu Visitation und Reform anderer Ordensstifte erhielten und durchführten und dass sie vom 17. Jahrhundert bis zur Aufhebung im Jahr 1802 als Generalvikare des Abtes von Prémontré in den Zirkarien Westfalen, Ilfeld und Wadgassen mit weitreichenden Vollmachten fungierten. Der hier publizierte Personenkatalog liefert in zwei Teilbänden Informationen zum Personal des Konvents. Die Viten der Pröpste und Äbte sind im ersten Teil abgehandelt, der zweite Teil enthält die biographischen Informationen zu den Chorherren des Stifts. Die Besitzungen des Prämonstratenserstifts Steinfeld sind separat im dritten Supplementband der Germania Sacra aufgearbeitet.
Keywords: steinfeld

Coverham Abbey - one of North Yorkshire's ancient gems - Lloyd, Chris (Darlington and Stockton Times, 2018)
Keywords: coverham

The Arnstein Bible: a grand monastic Bible - Doyle, Kathleen (British Library Medieval Manuscripts Blog, 2018)
Keywords: arnstein

The Tongerlo Apocalypse in the 16th and 17th Centuries - Kidd, Peter (Medieval Manuscripts Provenance, 2018)
Keywords: tongerlo

A Previously Unrecognised Tongerlo Provenance - Kidd, Peter (Medieval Manuscripts Provenance, 2018)
Keywords: tongerlo

Historie van Altforst: boerderijen (Kwekkertje: Dorpsblaadje van Altforst, 2018)
Keywords: altforst

L’ancien monastère Ste-Marguerite de Crécy à Brécy-Brières - Grossin, Emmanuel (Le Curieux Vouzinois, 2018)
Keywords: crécy

More stained glass fragments from Park Abbey (Leuven) discovered in Quebec - LaBrecque, Claire (Vidimus, 2018)
Keywords: park

Essai sur le patrimoine temporel de l'abbaye d'Arthous (XIIe-XVe s.) - Abadie, Stéphane (Bulletin de la Société de Borda, 2018)
Keywords: arthous

La mobilité d'un abbé au XVe siècle. Itinéraires et liens de communications de Thierry de Tuldel - Appelmans, Janick (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: park

Sœurs et pères en détresse: les prémontrés des anciens Pays-Bas face aux guerres, catastrophes et calamités - Appelmans, Janick (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: 🇳🇱 netherlands (general)

Kísérlet a bárdudvarnok-szentbenedeki premontrei prépostság környezeti rekonstrukciójára - Aradi, Csilla M.; Molnár, István (Genius loci -- Laszlovszky 60, 2018)
[An attempt to reconstruct the environment of the Premonstratensian abbey of Bárdudvarnok-Szentbenedek]
Keywords: kaposfő

Beauport. L'abbaye prémontrée de Bretagne. Histoires et vie quotidienne - Ballini, Annie-Claude (Association des amis de l'abbaye de Beauport, 2018)
Keywords: beauport

The Abbey of Meszes: New Insights on the Site Location - Bencze, Ünige (Genius loci – Laszlovszky 60, 2018)
Keywords: meszes

Das Prämonstratenserkloster Langen zwischen dem 14. und 16. Jahrhundert. 3: Die versuchte Übertragung von 1434: Akteure und Konsequenzen - Bley, Matthias (Emder Jahrbuch, 2018)
Keywords: langen

Die Bibliothek des Prämonstratenser-Stifts Heiligenberg - Bösche, Hartmut (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg/Mons Sanctae Mariae: erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: heiligenberg

San Norberto en algunas estampas flamencas del siglo XVII - Calvo Portela, Juan Isaac (Espacio, Tiempo y Forma. Serie VII, Historia del Arte, 2018)
Keywords: 👤 norbert of xanten

Uit het Regionaal Archief Nijmegen. Het ‘gevluchte’ archief van het nonnenklooster van de heilige Maria Magdalena te Nijmegen (1250-1562) - Camps, Rob (Jaarboek Numaga, 2018)
Keywords: nijmegen

Problem genezy formalnej prezbiterium w krakowskim kościele Norbertanek na Zwierzyńcu - Cierpisz, Szymon (Rocznik krakowski Towarzystwo Miłośników Historii i Zabytków Krakowa, 2018)
Keywords: zwierzyniec

Weißenau, Prämonstratenserkloster, Teil 3: Akten: 1152-1809 - Clauß, Susanne; Zausch, Marion; Löffler, Gabriele (Repertorien. Bestand B. Hauptstaatsarchiv Stuttgart, 2018)
Keywords: weissenau

Premonstratensian Settlement in the Czech Lands and Ireland, 1142-1250 - Clyne, Miriam (Journal of Medieval Monastic Studies, 2018)
The settlement of Premonstratensian canons and nuns is addressed against the backdrop of the political and ecclesiastical settings of the Czech Lands and Ireland. Colonization was accomplished through political alliances, religious circles, and interaction with the central authority at Prémontré during transitional phases of diocesan reform in Bohemia, Moravia, and Connacht, and Anglo-Norman acculturation in Ulster. The letters of the father abbot at Steinfeld and the abbots of Prémontré indicate their concerns for the future prospects of the distant monasteries, the needs of new communities, and how they reacted in different ways to maintain standards of uniformity and discipline.
Keywords: 🇨🇿 czechia (general); 🇮🇪 ireland (general)

Az ócsai premontrei prépostság régészeti kutatása - Csoltkó, Emese (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The village of Ócsa is situated to the south of Budapest in Pest County. The first mention of the existence of the Premonstratensian provostry is dated to 1234 in the so-called Catalogue of Ninive, which mentions that Ócsa is the filial of the convent of Jászó ( Jasov, Slovakia). The church with three naves and two towers at its western facade was built in the first half of the 13th century. During the construction works there were some modifications in the original plans, as the church was planned with another vaulting section towards at the west, but that was, along with the vaulting of the naves, never finished. Minor reconstruction works can be dated to the Middle Ages; for example wall-paintings and the Gothic pastoforium. The Premonstratensians left Ócsa before the Ottoman occupation period, but as a parish church, it didn’t lose the function which is attested by the 15th century demolition of the rood-screen. The church was used by the Calvinist congregation since 1560. As part of the preparation for the reconstruction works, there was archaeological research between 1986 and 1992 which was led by Juan Cabello. This included a systematic, full-scale excavation in the church and in the churchyard. In the course of the excavation, the monastery building with the one side and three pit houses from the 12th–13th century was found. The surrounding and inside of the church were used as a cemetery. The first reconstruction work was realized in the second half of the 18th century ( József Teleki’s works between 1774 and 1777). In the 18th century the church was damaged by natural disasters like lightning and fire. Thus another renovation was necessary, led by Ottó Tandor (1897–1900). In 1909 Ottó Sztehlo renewed the damaged northern portal. The elevation of the towers of the church was carried out by Ernő Foerk in 1923. Finally, the recent renovation of the church was conducted by Tibor Gál between 1989 and 1995.
Keywords: ócsa

Archeologia a San Cataldo – scavi e scoperte - Cucco, Rosa Maria; Correra, Marco (Notiziario Archeologico 41/2018 della Soprintendenza di Palermo, 2018)
Keywords: terrasini

"He proved to be an inseperable travel companion": Emo of Wittewierum and his Rome journey in 1211-1212 - De Boer, Dick (Gender, Companionship, and Travel: Discourses in Pre-modern and Modern Travel Literature, 2018)
Keywords: bloemhof

De rots van Floreffe en de bouwstenen van de abdij - De Ceukelaire, Marleen (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Vloeren in de abdij van Floreffe - De Ceukelaire, Marleen (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Die Prämonstratenser-Abtei von Fontaine-André - De Reynier, C. (Archaologie der Schweiz, 2018)
Keywords: fontaine-andré

De abdij van Floreffe waar de stenen en de dakkappen de weg wijzen naar de middeleeuwen - Doperé, Frans (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Die Prämonstratenser in Sachsen - Eick, Stefan (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg/Mons Sanctae Mariae: erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: 🇩🇪 germany (general)

Exkurs: Die geistlichen Predigten der Chorherren in Heiligenberg - Eick, Stefan (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg/Mons Sanctae Mariae: erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: heiligenberg

Bestattungen des Stader Klosterfriedhofes St. Georg entdeckt - Finck, Andrea (Archäologie in Niedersachsen, 2018)
Keywords: stade

Szent Euszták és vértanú társai prépostság | Háros-sziget, Budapest XXII. - Galuska, Tünde (A pálos rend építészeti emlékei, 2018)
Keywords: csút

Spätgotische Handwerkergraffiti in der ehemaligen Klosterkirche St. Katharina in Wenau (Kreis Düren) - Heckner, Ulrike (Historische Graffiti als Quellen : Methoden und Perspektiven eines jungen Forschungsbereichs : Beiträge der Konferenz am Institut für Klassische Archäologie der LMU München, 20.-22. April 2017, 2018)
Keywords: wenau

MA-XRF investigation of the Altenberg Retable from 1330 - Hoffmann, P.; Flege, S.; Ensinger, W.; Wolf, F.; Weber, C.; Seeberg, S.; Sander, J.; Schultz, J.; Krekel, C.; Tagle, R.; Wittkopp, A. (X-Ray Spectrometry, 2018)
The Altenberg Retable is one of the most important works of German art from the early 14th century. Composed of a shrine, a Madonna figure, and painted wings, it once adorned the high altar of the convent church in Altenberg/Lahn. The side and rear walls of the shrine were overpainted in 1609. Although conventional methods such as infrared reflectography and X-ray radiography could not reveal the underlying medieval paint layer, we succeeded by conducting μ-X-Ray fluorescent studies. The latter measurements included a handheld spectrometer as well as μ-X-Ray fluorescent large area scanner. Nine sections of the side and rear walls were examined as well as a field on one of the wings (as a reference). In each section, spectra were recorded that comprised about 20 elements ranging from K to Bi. Maps of Ca, Fe, Co, Cu, Zn, As, Hg, and Pb were evaluated and interpreted on the basis of the results of prior color sampling analysis. By superposing several element maps, the original medieval iconographic program with its rows of standing saints could be revealed. With the help of iconographic comparison, these saints could be identified: St. Christopher in the central part of the rear wall, flanked by the 4 female saints Clare, Agnes, Dorothy, and Barbara. On the side walls, the apostles Peter and Paul, as well as the deacons Stephen and Lawrence were depicted. Discussed are not only different scenarios of usage for these images behind the altar but also the limits and possibilities of the measurement technology in this specific application.
Keywords: altenberg

Eine hochmittelalterliche Warmluftheizung im Arnsberger Kloster Wedinghausen - Holtfester, Ulrich (Archäologie in Westfalen-Lippe, 2018)
Keywords: wedinghausen

Les grandes heures de l'Abbaye Royale Notre-Dame d'Abbecourt, Orgeval-Yvelines - Hubert, Jeannine (Association Histoire d'Orgeval, 2018)
Keywords: abbecourt

Heiligenbergs Gründung vor dem Hintergrund der Reichsgeschichte in der Zeit um 1218 - Hucker, Bernd Ulrich (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg, Mons Sanctae Mariae : erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: heiligenberg

The Stained Glass Biblia Pauperum Windows of Steinfeld Abbey: Monastic Spirituality, Salvation History and the Theological Imagination - Hyland, William (The Moving Text: Interdisciplinary Perspectives on David Brown and the Bible, 2018)
Keywords: steinfeld

Die Stellung der Abtei Steinfeld im Prämonstratenserorden - Joester, Ingrid (Analecta Praemonstratensia, 2018)
Keywords: steinfeld

St. Nikolaus in Köln-Dünnwald: Pfarrkirche und ehemalige Klosterstiftskirche - Juraschek-Eckstein, Markus (Kunstverlag Josef Fink, 2018)
Keywords: dünnwald

Lateinische Rivalen in Konstantinopel: Anselm von Havelberg und Hugo Eterianus - Kapriev, Georgi (Recherches de théologie et philosophie médiévales. Bibliotheca, 2018)
Keywords: 👤 anselm of havelberg

Les épisodes noirs de la blanche abbaye d'Ardenne - Khedine, Françoise (Actes officiels du 39e colloque du Centre d'études et de recherches prémontrées. Guerres, catastrophes et calamités. Troyes, 2013, 2018)
Keywords: ardenne

Penitential punishment and purgatory: a drama of purification through pain - Kirakosian, Racha (Punishment and Penitential Practices in Medieval German Writing, 2018)
Keywords: 👤 christina of hane

Adalékok a jászói Keresztelo Szent János premontrei monostor középkori történelméhez - Kotrusová, Júlia (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The Monastery of St. John the Baptist in Jasov belongs among the oldest Premonstratensian monasteries in modern Slovakia. The circumstances surrounding the arrival of Premonstratensians in Jasov and the year of foundation of the monastery are amongst the most debated problems in the history of the Jasov provostship. The source of these controversies is the fact that the foundation charter was not preserved. The opinions of historians on the foundation of the monastery vary. A number of historians assume that it was founded at the turn of the 12th and 13th centuries, possibly at the beginning of the 13th century. I argue that a charter issued by King Béla IV in 1255 can contribute to clarification of the foundation of the convent. The document re-establishes the originalprivileges of the monastery. The earliest references to Premonstratensian monasteries in Hungary is preserved in the Ninive catalogue, specifically in its second registry. The properties of the monastery also raise a number of questions. The institution owned properties of high value in the Middle Ages. The oldest mention of their estate possession dates back to the above mentioned charter issued by King Béla IV in 1255. The lands mentioned in the charter were compact. Besides the original property described by the charter, in 1255 lands were provided for the monastery that Béla acquired from Duke Coloman. During the medieval and early modern period Jasov was a central property of the Jasov provostship. Due to its location and its vicinity to the monastery, it became more and more prominent in the 13th century, when it gained urban privileges, most importantly market rights.
Keywords: jasov

Kláštor premonštrátov v Kláštore pod Znievom: stavebný vývoj v stredoveku - Kürthy, Luboš (Architektúra kláštorov a rehoľných domov na Slovensku : dejiny a pamiatková ochrana, 2018)
Keywords: klaštor pod znievom

Norbertanki płockie - Kuźniewska, Zofia H. (Rocznik Towarzystwa Naukowego Płockiego, 2018)
Keywords: płock

Krypta unter dem Turm der Stiftskirche in Flaesheim? - Laakmann, Heiner (Halterner Jahrbuch, 2018)
Keywords: flaesheim

Alleen God en de zon: negen eeuwen Hof te Kattem - Liedekerke, Luc Van (Luc Van Liedekerke, 2018)
Keywords: kattem

Die ehemalige Klosterkirche in Rumbeck bei Arnsberg, eine frühe Hallenkirche in Westfalen - Lobbedey, Uwe (Gotik : der Paderborner Dom und die Baukultur des 13. Jahrhunderts in Europa : Katalog zur Ausstellung im Erzbischöflichen Diözesanmuseum Paderborn, 2018)
Keywords: rumbeck

Floreffe sur le chemin de saint Norbert - Lombet, Jean (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Von Stiftern, Fälschern und Forschern. Die hochmittelalterlichen Urkunden für Cappenberg und ihre Bedeutung für das Stift und seine Geschichte - Lubich, Gerhard (... sich einen Kopf machen. Cappenberger Vorträge zum Mittelalter, 2018)
Keywords: cappenberg

The deeds of Count Ludwig of Arnstein (d. 1185) - Lyon, Jonathan R. (Noble Society : Five lives from twelfth-century Germany, 2018)
Keywords: arnstein

La fondation de l'abbaye de Beauport par le prince de Bretagne, Alain de Goëlo (1202) - Morvan, Frédéric (Église, religion, croyances du Moyen Âge à nos jours, 2018)
Keywords: beauport

Voneinander gelernt? Ein vergleichender Blick auf die Bildprogramme der Klosterbibliotheken von Wiblingen, St. Peter auf dem Schwarzwald, Bad Schussenried und ein Exkurs zu Weissenau - Mühleisen, Hans-Otto (Herrschaftswissen Bbibliotheks- und Archivbauten im Alten Reich, 2018)
Keywords: schussenried

The Leake Cartulary and the Derbyshire Estates of Welbeck Abbey - Munford, Anthony P.; Hopkinson, Aileen M. (Derbyshire Record Society Series, 2018)
Keywords: welbeck

Spätmittelalterliche Frömmigkeit im Prämonstratenserkloster Gramzow: eine Seelenmessenstiftung aus dem Jahr 1500 - Neitmann, Klaus (Angermünder Heimatkalender, 2018)
Keywords: gramzow

2018:084 - Abbots Road, Whiteabbey, Antrim - O'Regan, Christine (Excavations.ie, 2018)
Keywords: whiteabbey

Cutting their cloth: the Scottish Premonstratensians, c. 1150 to c. 1350 - Oram, Richard (Places of worship in Britain and Ireland, 1150-1350, 2018)
Keywords: 🇬🇧 great britain (general)

Spory cystersów sulejowskich i norbertanów witowskich w XIII i XIV w - Parol, Jakub (Nasza Przeszłość : studia z dziejów Kościoła i kultury katolickiej w Polsce, 2018)
Keywords: witów

Kardinalsunterschriften als Fälschungsindiz: das Privileg Eugens III. für das Stift Rot an der Rot (JL 9618) und seine Vorlagen - Petersen, Stefan (Archiv für Diplomatik, 2018)
Keywords: rot an der rot

San Pietro di Acqua Alta - Piselli, Daniele (Comunità laica e religiosa di Montegabbione: chiese ed abazie nei sec. XII-XIV, 2018)
Keywords: aqualta

Scheda: Kloster - Rittergut - Landwirtschaftlicher Betrieb. Erstmalige Erwähnung schon in einer Urkunde aus dem Jahr 1147 - Platte, Hartmut (Heimatkalender des Kreises Soest, 2018)
Keywords: scheda

L'abbaye Notre-Dame et Saint-Jean-Baptiste de Basse-Fontaine [commune de Brienne-la-Vieille]. L'abbaye Notre-Dame de Beaulieu [commune de Trannes] - Plouvier, Martine (Actes officiels du 39e colloque du Centre d'études et de recherches prémontrées. Guerres, catastrophes et calamités. Troyes, 2013, 2018)
Keywords: basse fontaine; beaulieu

“Copy destroyed”: de lotgevallen van een verdwenen incunabel - Popkema, Anne Tjerk; De Vries, Herre (De Gulden Passer, 2018)
[“Copy destroyed”: the fate of a missing incunabula]
Keywords: averbode

Sapientes Nostri. I Dialogi (O Antikeimenon) di Anselmo di Havelberg e la circolazione dei testi di Gregorio di Nazianzo nell'Europa latina del XII secolo - Saccenti, Riccardo (Revue d'histoire ecclésiastique, 2018)
Keywords: 👤 anselm of havelberg

Stiftskirche Cappenberg - Saeger, Klaus (Kleine Kunstführer, 2018)
Keywords: cappenberg

The Translation of St. Norbert’s Remains to Prague in 1627: True account of a letter sent by St. Michael’s of Antwerp to the Canons Regular of the Monastery of Saint Norbert of Madrid - Sands, Rosemary (Communicator: The English Speaking Circary of the Order of Prémontré, 2018)
Keywords: 👤 norbert of xanten

Geschiedenis van de twee watermolens en van de houten korenwindmolen van de abdij van Ninove te Ninove - Souffreau, Georges Léon (Georges L. Souffreau, 2018)
Keywords: ninove

Zabytkowe hafty norbertanek żukowskich. Stan badań po czterdziestu latach - Stanilewicz, Karolina (Folia Historica Cracoviensia, 2018)
Keywords: żukowo

Prämonstratenser-Klöster Nova Rise und Geras im Vergleich von der Gründung bis zur Gegenwart - Štroblová, Lada (Masaryk University, 2018)
Keywords: geras; nová říše

Gyulafirátót, avagy a rendi építészeti hagyományok átjárhatósága - Szakács, Béla Zsolt (Genius Loci. Laszlovszky 60, 2018)
(Gyulafirátót or the permeability of the monastic architectural traditions)
Keywords: gyulafirátót

Liber ordinarius klasztoru premonstratensów na Ołbinie. Przyczynek do dalszych badań nad rękopisem - Szukiel, Piotr (Od Benedyktynów i Premonstratensów do Salezjanów: dzieje kościoła i parafii Św. Michała Archanioła na wrocławskim Ołbinie : materiały konferencji naukowej z okazji 70-lecia obecności salezjanów na wrocławskim Ołbinie (Wrocław, 28-29 kwietnia 2017 r.), 2018)
Keywords: wrocław

Autels et cheminées marbrières dans l’abbaye de Floreffe - Tourneur, Francis (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

A levéltárak titkos élete. A Csornai Premontrei Apátság levéltárainak évszázadai - Vajk, Ádám (Soproni Szemle: Helytörténeti folyóirat, 2018)
[The secret life of archives. Centuries of the archives of the Premonstratensian abbey of Csorna]
Keywords: csorna

Geschreven bronnen over de bouw van de eerste Ninoofse abdijkerk - Van De Perre, Dirk (Het Land van Aalst, 2018)
Keywords: ninove

Het kaartenarchief van de Ninoofse abdij herbekeken - Van De Perre, Dirk (Het Land van Aalst, 2018)
Keywords: ninove

La position des abbayes prémontrées, en particulier celle de Ninove, pendant la guerre civile et religieuse dans les Pays-Bas (1578-1587) - Van De Perre, Dirk (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: ninove

Litomyšlské biskupství po roce 1421 - Večeře, Vojtěch (Studia Medievalia Bohemica, 2018)
Keywords: litomyšl

Un scribe au travail pour deux abbayes: Gérard de Cologne, chanoine prémontré (fin XIIIe siècle), à travers ses livres d’archives - Verpeaux, Nathalie (Scriptorium, 2018)
Keywords: 📚 premonstratensian (general)

Kloster Reichenstein, Monschau - Fortschreibung der Denkmaleintragung und Ergänzung der Außenanlagen - Walter, Kerstin (Jahrbuch der rheinischen Denkmalpflege, 2018)
Keywords: reichenstein

"Ducalis Parthenon Domûs Dei" : uwagi o architekturze i wymowie ideowej norbertańskiego kompleksu klasztornego w Czarnowąsach - Wojtyla, Arkadiusz (Sztuka dawnego Opola, 2018)
Keywords: czarnowąsy

Die Prämonstratenserstifte Ober- und Nieder-Ilbenstadt - Wolf, Jürgen Rainer (Germania Sacra, 2018)
Keywords: ilbenstadt; niederilbenstadt

Henry Zdik, bishop of Olomouc and Premonstratensian - Wolverton, Lisa Ann (Portraits of Medieval Eastern Europe, 900-1400, 2018)
Keywords: 📚 premonstratensian (general)

Z histórie opevneného kláštora v Bzovíku - Žažová, Henrieta; Maliniak, Pavol; Kožiak, Rastislav (OZ Pod hradom, 2018)
Keywords: bzovík

Premonstrátský klášter a kostel sv. Jiljí v Milevsku - Zelenková, Pavla (Opera Facultatis theologiae catholicae Universitatis Carolinae Pragensis. Historia et historia artium, 2018)
Keywords: milevsko